Promotion of vesicular zinc efflux by ZIP13 and its implications for spondylocheiro dysplastic Ehlers–Danlos syndrome - Jeong, Jeeyon (National Academy of Sciences, 2012)
Zinc is essential but potentially toxic, so intracellular zinc levels are tightly controlled. A key strategy used by many organisms to buffer cytosolic zinc is to store it within vesicles and organelles. It is yet unknown whether vesicular or organellar sites perform this function in mammals. Human ZIP13, a member of the Zrt/Irt-like protein (ZIP) metal transporter family, might provide an answer to this question. Mutations in the ZIP13 gene, SLC39A13, previously were found to cause the spondylocheiro dysplastic form of Ehlers–Danlos syndrome (SCD-EDS), a heritable connective tissue disorder. Those previous studies suggested that ZIP13 transports excess zinc out of the early secretory pathway and that zinc overload in the endoplasmic reticulum (ER) occurs in SCD-EDS patients. In contrast, this study indicates that ZIP13’s role is to release labile zinc from vesicular stores for use in the ER and other compartments. We propose that SCD-EDS is the result of vesicular zinc trapping and ER zinc deficiency rather than overload.